Sustainable Location Identification Decision Protocol (SuLIDeP) For Determining The Location Of Recycling Centres In A Circular Economy - Mohamed Sultan, Al Amin; Mativenga, Paul Tarisai (Elsevier Ltd., 2019)
Landfill restrictions on certain materials and products have provided the impetus to seek for a more sustainable utilisation of waste in a circular economy. These restrictions compounded with legislation and value factors necessitate an urgent solution to address the issue of carbon or glass fibre reinforced composite waste disposal. There is currently no mutual agreement on waste ownership among stakeholders. This study examined composite manufacturers in the United Kingdom and determined the waste volumes available within these companies. A new approach that combined mathematical modelling of supply chain complexity, centre-of-gravity method and K-Means algorithm was developed to determine the optimum location of third parties that could process waste for a number of supply chain providers. The paper is a presentation of new knowledge and proposes a scientific approach for identifying possible optimum locations for recycling centres. More significantly, this process could be used for clustering and reducing supply chains complexity to enable the setting up of multiple and optimally located recycling centres. The results have indicated that the approach could minimize carbon footprint and greenhouse gas emission associated with transporting cores or waste to processing centres. This work is of generic importance that could be implemented across other waste and aspects of a circular economy such as remanufacturing.